Prevalence of Autism Spectrum Disorder in Children in Andalusia (Spain). - Villegas-Lirola, Francisco (Journal of Autism & Developmental Disorders, 2023)
Autism Spectrum Disorder (ASD) is socially relevant because of its number and the intensity of the medical and socio-educational response it requires. In Andalusia, one in 70 children will be diagnosed with ASD in 2021. It is much more frequent in boys than in girls, being 5.91 times more likely to present it as a boy than as a girl. The age of diagnosis is increasingly younger, standing at 4.4 years. In more than half of primary schools and more than 75% of secondary schools there are an average of three students with ASD per school. It is necessary to develop a network of preferential care centers for students with ASD to generalize specialized care in ordinary modalities.